ANALYSIS OF FOOD FULFILLMENT IN PERI-URBAN AREAS OF SURAKARTA CITY IN 2025 - Rita Noviani; Chatarina Muryani; Sugiyanto Sugiyanto; Singgih Prihadi; Imasti Dhani Pratiwi; Istiyanti Nur Marfu'ah (Universitas Sebelas Maret (UNS), 2026)
The rapid growth of urbanisation in the city of Surakarta has led to the conversion of agricultural land into residential and industrial areas, significantly impacting the food security of peri-urban areas. This study aims to analyse the land carrying capacity (σ), optimal population, and agricultural land needs for the viability of residents in the peri-urban area of Surakarta City. Data were obtained through the analysis of Sentinel-2A imagery and population statistics, utilising a guided classification approach with the CART algorithm. The results showed that most villages in eight peri-urban sub-districts were in a state of food deficit, with a σ value of < 1, indicating a high dependence on external food supply. Only a few villages in the northern part of Gondangrejo show surplus status. This condition highlights the urgency of implementing a strategy to protect agricultural land and control population growth rates to achieve sustainable food security in suburban areas. These findings make an important contribution to spatial planning and food policy in metropolitan areas.